Antibacterial effect and tetracycline release of poly(Ɛ-caprolactone) matrices obtained by iodine polymerization (Research, Society and Development, 2022)
The development of devices to controlled the release of drugs are in constant technological innovation. The aim is to improve the release of drugs on target areas. Poly (ε-caprolactone) (PCL) has been widely investigated because of degradation rate, biocompatibility, availability, no toxicity, cost and good adhesion to a large number of drugs. Thus, in the present study was associated polymer PCL with antibiotics tetracycline as local delivery system. PCL was obtained by ring-opening polymerization of monomer Ɛ-caprolactone (Ɛ-CL). The samples were characterized by fourier transformed infrared (FTIR), differential scanning calorimetric (DSC), thermogravimetric analyses (TGA) and X-ray diffraction analysis (X-rays). Likewise, was investigated antimicrobial activity against gram-positive bacteria (S. aureus) and gram-negative bacteria (E. coli, P. mirabilis, P. aeruginosa and K. pneumoniae). According to the results, the antibiotics tetracycline has been successfully incorporated to PCL matrices. They release tetracycline in the ideal rates and shows antibacterial activity. So, this material has a potential to been used in implants for drug release.